GRAAL: Gem Reconstruction And Analysis Library. (April 2020) - Farinelli, R.; Alexeev, M.; Amoroso, A.; Bagnasco, S.; Baldini Ferroli, R.; Balossino, I.; Bertani, M.; Bettoni, D.; Bortone, A.; Bianchi, F.; Calcaterra, A.; Cerioni, S.; et al.
Abstract: Micro Pattern Gas Detectors (MPGD) are the new frontier in gas trackers. Among this kind of devices, the Gas Electron Multiplier (GEM) chambers are widely used. The experimental signals acquired with the detector must obviously be reconstructed and analysed. In this contribution, a new offline software to perform reconstruction, alignment and analysis on the data collected with APV-25 and TIGER ASICs will be presented. GRAAL (Gem Reconstruction And Analysis Library) is able to measure the performance of a MPGD detector with a strip segmented anode (presently). The code is divided in three parts: reconstruction, where the hits are digitized and clusterized; tracking, where a procedure fits the points from the tracking system and uses that information to align the chamber with rotations and shifts; analysis, where the performance is evaluated (e.g. efficiency, spatial resolution, etc.). The user must set the geometry of the setup and then the program returns automatically the analysis results, taking care of different conditions of gas mixture, electric field, magnetic field, geometries, strip orientation, dead strip, misalignment and many others.